Targeted treatment of autoimmune cytopenias in primary immunodeficiencies - Pacillo, Lucia; Giardino, Giuliana; Amodio, Donato; Giancotta, Carmela; Rivalta, Beatrice; Rotulo, Gioacchino Andrea; Manno, Emma Concetta; Cifaldi, Cristina; Palumbo, Giuseppe; Pignata, Claudio; Palma, Paolo; Rossi, Paolo; et al. (Frontiers in Immunology, 2022)
Primary Immunodeficiencies (PID) are a group of rare congenital disorders of the immune system. Autoimmune cytopenia (AIC) represents the most common autoimmune manifestation in PID patients. Treatment of AIC in PID patients can be really challenging, since they are often chronic, relapsing and refractory to first line therapies, thus requiring a broad variety of alternative therapeutic options. Moreover, immunosuppression should be fine balanced considering the increased susceptibility to infections in these patients. Specific therapeutic guidelines for AIC in PID patients are lacking. Treatment choice should be guided by the underlying disease. The study of the pathogenic mechanisms involved in the genesis of AIC in PID and our growing ability to define the molecular underpinnings of immune dysregulation has paved the way for the development of novel targeted treatments. Ideally, targeted therapy is directed against an overexpressed or overactive gene product or substitutes a defective protein, restoring the impaired pathway. Actually, the molecular diagnosis or a specific drug is not always available. However, defining the category of PID or the immunological phenotype can help to choose a semi-targeted therapy directed towards the suspected pathogenic mechanism. In this review we overview all the therapeutic interventions available for AIC in PID patients, according to different immunologic targets. In particular, we focus on T and/or B cells targeting therapies. To support decision making in the future, prospective studies to define treatment response and predicting/stratifying biomarkers for patients with AIC and PID are needed.